PANDANGAN DEWAN PIMPINAN WILAYAH FRONT PEMBELA ISLAM KALIMANTAN BARAT TERHADAP RANCANGAN UNDANG – UNDANG HALUAN IDEOLOGI PANCASILA - Viqri Rahmad Satria (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
This study aims to understand the West Kalimantan Front Pembela Islam Regional Representative Council opinion about Rancangan Undang-Undang Haluan Ideologi Pancasila which makes Islamic organizations strongly reject it. Data were collected through observation and interview with the West Kalimantan Front Pembela Islam Regional Representative Council secretary.Other findings: 1) RancanganUndang-Undang Haluan Ideologi Pancasila is very contradictory to the existing norms in Indonesia, especially the Pancasila ideology, 2) the communist ideology might rise if Rancangan Undang-Undang Haluan Ideologi Pancasila is accepted because there is no TAP MPRS No XXV / 1966 in it whichrules the dissolution of the Indonesian Communist Party and the prohibition of the ideology of communism / Marxism, 3) The mixing of Trisila with cultural devotion because the concept of religion cannot develop with culture.The suggestion of this research to the House of Representatives in drafting a law must apply Pancasila as the basis of the State and Pancasila must be positioned as the source of all sources in Indonesia, the Pancasila Ideology Direction Bill is only in the interest of power.